2021
DOI: 10.51173/jt.v3i1.270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silver-Zinc Zeolite Incorporation on Shear Bond Strength of Silicon Cold Cure Soft Liner

Abstract: Back ground: Reduction of a durable bond to acrylic denture base is the main problem associated with soft liner materials. Purpose: Evaluation of the influence of addition of Ag-Zn Zeolite on shear bond strength of silicon cold cure   soft liner. Approach: thirty specimens   of silicon cold cure  soft liner were constructed for shear bond- strength test and divided into three groups: Control groups: 10 specimens without incorporation of Ag-Zn Zeolite, Experimental group: 10 specimens with 0.5% by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The result of this study is comparable with Ari et al who found decreasing surface roughness and dimensional change of the casting after the addition of zeolite to phosphatebonded investment due to its molecular sieve property [33]. Furthermore, Sadeq and Hummudi found a significant improvement in shear bond strength of the HC silicon soft liner after incorporation of 0.50 wt.% and 0.75 wt.% Ag-Zn zeolite [24]. However, in the case of CC resin, the same authors found that only 0.75 wt.% Ag-Zn zeolite can generate a surface roughness significantly lower than that of the pure CC resin [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The result of this study is comparable with Ari et al who found decreasing surface roughness and dimensional change of the casting after the addition of zeolite to phosphatebonded investment due to its molecular sieve property [33]. Furthermore, Sadeq and Hummudi found a significant improvement in shear bond strength of the HC silicon soft liner after incorporation of 0.50 wt.% and 0.75 wt.% Ag-Zn zeolite [24]. However, in the case of CC resin, the same authors found that only 0.75 wt.% Ag-Zn zeolite can generate a surface roughness significantly lower than that of the pure CC resin [24].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Sadeq and Hummudi found a significant improvement in shear bond strength of the HC silicon soft liner after incorporation of 0.50 wt.% and 0.75 wt.% Ag-Zn zeolite [24]. However, in the case of CC resin, the same authors found that only 0.75 wt.% Ag-Zn zeolite can generate a surface roughness significantly lower than that of the pure CC resin [24]. Ning et al found that the surface roughness of zeolite-polyamide thin-film nanocomposite membranes (TFN) increased by increasing the zeolite loading as a result of the zeolite incorporation, which was characterised by a greater nodular appearance on the surface of TFN membranes [34].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation